Speech Acts and Argumentative Resources in the Speeches Given in Front of the European Parliament by King Juan Carlos I and by King Felipe VI (Journal of Advanced Research in Social Sciences, 2021)
This paper focuses on comparing the speeches given in front of the European Parliament by King Juan Carlos I on the 14th of May 1986 and by King Felipe VI on the 7th of October 2015 from a pragma-rhetoric perspective. It highlights certain speech acts that may constitute the backbone of the two speeches, as they refer to key topics such as terrorism, the preservation of European values, a more integrated Europe, etc. Moreover, it also attempts to identify significant argumentative resources that were used such as rhetorical figures and various types of arguments. Both speeches reflect some of the issues that the European Union had to tackle at the time they were delivered. King Juan Carlos I urges for a more united Europe and he puts emphasis on the technological challenges that lie ahead. He uses anaphors, a paradox and the ad consequentiam argument. King Felipe VI points out the need of the European Union to identify new internal and external objectives in a more globalized world. He also states that, by joining their forces together, the European states can offer help to the thousands of refugees who were migrating back then mostly from Syria, Afghanistan and Iraq so as to escape war. King Felipe VI uses in his argumentation anaphors, the circular reasoning fallacy, the ad consequentiam argument and the appeal to authority. As a discursive strategy, he mentions that the European Union is “our great common project”, making thus reference to the concept of “project of life” as it was defined by the Spanish philosopher José Ortega y Gasset. Both orators employ personifications of Spain. They both throw a strong light on the role of Spain within the European Union. The text analysis application AntConc is used in order to detect the most used words in their speeches.